Points of commitment to reproductive events as a tool for analysis of the cell cycle in synchronous cultures of algae - Vítová, M; Zachleder, V (Folia microbiologica, 2005)
Methods for determining the points of commitment for cell division are described for species of green algae dividing by multiple fission, both forming coenobia (Scenedesmus quadricauda) and releasing single daughter cells (Chlamydomonas eugametos, Scenedesmus armatus). The timing of commitment points was followed in detail in synchronous cultures of S. quadricauda grown under various light intensities, illumination regimes, and temperatures. The pre-commitment periods were rate limiting, while the post-commitment periods remained more or less constant under various light intensity. Temperature, on the other hand, affected both periods in a similar manner and they were prolonged with decreasing temperature.
Keywords: buněčné dělení; Animals; buněčný cyklus; Light; Temperature; Chlamydomonas; zvířata; světlo; kultivační média; Cell Division; teplota; Culture Media; Scenedesmus; Cell Cycle